FRICTION-WEAR CHARACTERISTICS OF PLASMA NITRIDED COLD WORK TOOL STEELS - Hakan Aydın; Ahmet Yılmaz (Uludağ University Journal of The Faculty of Engineering, 2020)
D2, D6 and Calmax cold work tool steels were heat treated in vacuum hardening, made grinding and plasma nitrided in 75% N2 + 25% H2 atmosphere at 450 °C for 12 h at 2 mbar. Characterization of samples has been carried out by means of surface roughness, microstructure, microhardness and wear-friction. Wear-friction characteristics of samples have been investigated using a ball-on-disc tribosystem with a WC-Co ball. Plasma nitriding increased the surface roughness of samples. However, this effect was decreased with higher surface roughness of base metal. Fe4N (γ'), Fe3N (ε) and CrN phases were obtained on the surfaces of samples. Higher surface hardness was obtained in the plasma nitrided D2 and D6 steels. No significant mass loss was observed in the ball on-disc tribosystem. So, the wear of samples was characterized with the worn surfaces using a scanning electron microscope (SEM). Plasma nitriding improved the wear resistance and decreased the friction coefficient of steels. Plasma nitrided D2 steel showed the highest wear resistance, whereas plasma nitrided Calmax steel exhibited the lowest wear resistance. However, plasma nitrided Calmax tool steel had relatively lower friction coefficient than the other plasma nitrided steels. In general, brittle layer fractures have determined the friction coefficient.